North Atlantic forcing of moisture delivery to Europe throughout the Holocene - Smith, Andrew C.; Wynn, Peter M.; Barker, Philip A.; Leng, Melanie J.; Noble, Stephen R.; Tych, Wlodek (Nature Publishing Group, 2016)
Century-to-millennial scale fluctuations in precipitation and temperature are an established feature of European Holocene climates. Changes in moisture delivery are driven by complex interactions between ocean moisture sources and atmospheric circulation modes, making it difficult to resolve the drivers behind millennial scale variability in European precipitation. Here, we present two overlapping decadal resolution speleothem oxygen isotope (δ18O) records from a cave on the Atlantic coastline of northern Iberia, covering the period 12.1–0 ka. Speleothem δ18O reveals nine quasi-cyclical events of relatively wet-to-dry climatic conditions during the Holocene. Dynamic Harmonic Regression modelling indicates that changes in precipitation occurred with a ~1500 year frequency during the late Holocene and at a shorter length during the early Holocene. The timing of these cycles coincides with changes in North Atlantic Ocean conditions, indicating a connectivity between ocean conditions and Holocene moisture delivery. Early Holocene climate is potentially dominated by freshwater outburst events, whilst ~1500 year cycles in the late Holocene are more likely driven by changes internal to the ocean system. This is the first continental record of its type that clearly demonstrates millennial scale connectivity between the pulse of the ocean and precipitation over Europe through the entirety of the Holocene.